The recognition of the leaf size determines the egg cluster size while leaf abundance is correlated to the laying frequency for Luehdorfia puziloi (Lepidoptera: Papilionidae) oviposition - Kim, D.S., Kyungpook National University, Daegu , Republic of Korea; Park, D.S., KRIBB, Daejeon , Republic of Korea; Koh, J.K., Daegu Haany University, Gyeongsan. Republic of Korea (Journal of Ecology and Environment, 2013)
The life cycle of butterflies is closely related to the growth of food plants and, through a prolonged coevolutionary process, has undergone an ecological adaptation. So, it is important that control the egg-laying number and place to secure enough food plant by female adult to guarantee the survival of the larvae. To study whether oviposition control of the Luehdorfia puziloi takes into greater consideration food plant leaf biomass or leaf abundance, correlation among the egg cluster size, the leaf size, and the number of leaves around egg clusters was investigated. According to the results, the egg clusters size exhibited positive correlation with the leaf size of food plants on which eggs had been laid but did not do so with the number of surrounding leaves. In addition, the number of egg clusters laid exhibited positive correlation with the number of surrounding food plant leaves but not with the leaf size on which eggs had been laid. Consequently, for the Luehdorfia puziloi, the females’ recognition of the leaf size seems to be the most important factor in the egg cluster size, and the number of egg clusters had positive correlation with food plant density per unit area.